Pengaruh Kinerja Keuangan Daerah Terhadap Pertumbuhan Ekonomi Tahun 2013-2022 - Agis Eles Sevigo; Nurul Lathifah (Journal of Trends Economics and Accounting Research, 2024)
The study aims to test the impact of regional financial performance on economic growth in Sidoarjo District in 2013-2022. This research uses a quantitative approach with a type of descriptive research. The number of samples in this study is 34, which is obtained through the method of interpolation with reference to the APBD budget data of Sidoarjo district from the year 2013-2022. The study used a double linear regression analysis processed using SPSS 25 software. The data collection was carried out with a library study, with data sources coming from the Central Statistical Authority (BPS) and the Directorate-General for Financial Balances (DJPK) of the Ministry of Finance. The results of this study show that the significance value of the f test is 0.002, so it can be concluded that regional financial performance consisting of the PAD effectiveness ratio, APBD efficiency ratio, and independence ratio simultaneously has a significant effect on economic growth in Sidoarjo Regency. The significance of the t test results is that the PAD effectiveness ratio is 0.842 and the APBD efficiency ratio is 0.984, so that the PAD effectiveness ratio and APBD efficiency ratio have no effect on economic growth in Sidoarjo Regency. Meanwhile, the significance value of the independence ratio t test is 0.000, so the independence ratio has an effect on economic growth in Sidoarjo Regency.